Czech translations of Jean-Arthur Rimbaud's poem the Drunken Boat after the Second World War - Drskova, Katerina (Romanica Olomucensia, 2017)
This article focuses first on the history of the Czech reception of the work of Jean-Arthur Rimbaud and on the modifications of its interpretation, from the earliest mention concerning Rimbaud to its present perception. Then, in this context, three Czech translations of the poem The Drunken Boat are analyzed, dating from the post-World War II period: those by Frantisek Hrubin (1956, 1961), Otto F. Babler (1981), and Gustav Francl (2008).
Keywords: Jean-Arthur Rimbaud; The Drunken Boat; literary translation; Frantisek Hrubin; Otto F. Babler; Gustav Francl